Methylenetetrahydrofolate Reductase Gene C677T Polymorphism–Dietary Pattern Interaction on Hyperhomocysteinemia in a Chinese Population: A Cross-Sectional Study - Leng, Song; Zhao, Ai; Zhang, Jian; Wu, Wei; Wang, Qian; Wu, Shan; Chen, Li; Zeng, Qiang (Frontiers in Cardiovascular Medicine, 2021)
Background and Aim: Hyperhomocysteinemia (Hhcy) has been recognized as a risk factor of several chronic diseases. There is accumulating evidence that both genetic and dietary factors had a notable impact on the risk of Hhcy. The present study aims to investigate the interaction effect on Hhcy between methylenetetrahydrofolate reductase (MTHFR) gene C677T polymorphism and dietary intake. Methods: Data were collected in a cross-sectional survey conducted in China. 3966 participants with complete information on sociodemographic characteristics, anthropometric measurements, and dietary intake were included in analyses. Dietary patterns were identified by factor analysis combined with cluster analysis. Blood samples were collected and MTHFR C677T genotypes were tested. Both the multiplicative statistical model and the additive model were conducted to investigate the interactive effects. Results: Proportions of MTHFR C677T genotypes among participants were 29.2% for TT, 47.4% for CT, and 23.3% for CC. Three dietary patterns were identified, including the balanced pattern, the snack pattern and the high-meat pattern. Compared with the balanced pattern, the other two patterns were associated with an elevated risk of Hhcy (the snack pattern: odds ratio [OR] 1.2, 95% confidence interval [CI] 1.0-1.5; the high-meat pattern: OR 1.3, 95%CI 1.1-1.6) after adjustment for age group, gender, residential region, and MTHFR C677T genotypes. Multiplicative interaction between the high-meat pattern and MTHFR 677TT genotype was observed, and synergistic effects between both the snack pattern and the high-meat pattern with MTHFR 677TT were identified. Conclusion: Our results indicated that MTHFR C677T polymorphism and dietary patterns had interactive effects on Hhcy among the Chinese population. Subsequent targeted and appropriate dietary guidelines should be recommended for high-risk populations or patients of Hhcy carrying specific genotypes.